Plasma chloroquine concentrations in young and older malaria patients treated with chloroquine. - Maitland, K; Williams, T; Kotecka, B; Edstein, MD; Rieckmann, K (1997)
Plasma chloroquine (CQ) concentrations were measured by bioassay in young (0-4 years, n = 9) and older (5-60 years, n = 21) patients from Vanuatu infected with malaria following treatment with 25 mg/kg CQ over 3 days. CQ concentrations in young children tended to be lower than in older patients at days 2, 3, 4 and 7 after onset of treatment, with no drug present in two young children on day 3 and in one child on day 7. The greater difficulty experienced by young children to ingest all of their prescribed medication could have contributed to the lower CQ concentrations observed in the younger age group. The possibility that sub-therapeutic CQ concentrations are responsible for treatment failures in young children should be considered in areas where a high degree of CQ resistance has not yet been established. In such areas, the presence or prevalence of CQ-resistant infections should not be based on treatment failures observed in young children unless it can be confirmed that adequate blood CQ concentrations were achieved after treatment.